Analysis of Purchasing Decisions in terms of Testimonials, Promotional Content, Endorsements (Study on Kediri Spicy Dumplings) - Ruminiege, Seiko Seikatsuno Heinz; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study's goal is to investigate the effects of endorsements, advertising, and endorsements on consumer purchasing decisions at Kediri Spicy Dumplings, a UMKM in the culinary sector. Design/Methode/Approach: This study employs a causality design and a quantitative methodology. Data were collected from 40 respondents who are followers of the Instagram account Kediri Spicy Dumplings. The coefficient of determination, hypothesis testing (t-test and F-test), and multiple linear regression tests are all part of the analysis process. Research Finding: The findings demonstrate that endorsements, advertising materials, and testimonies all significantly and favourably affect consumers' decisions to buy. Testimonials can increase consumer trust through customer experience, promotional content attracts attention through creativity and relevance, while endorsements by local influencers strengthen product visibility and credibility. Theoretical contribution/Originality: This research contributes to the consumer behaviour literature by exploring the combined effects of testimonials, promotional content, and endorsements in the context of digital marketing for UMKM. Practitioner/Policy implication: The findings provide practical insights for UMKM to implement effective digital marketing strategies by utilizing testimonials, promotional content, and influencer endorsements to improve competitiveness in the digital marketplace. Research limitation: This research only focuses on one UMKM in Kediri, so the findings cannot be generalized. Future research can include several UMKM  in various regions.